(untitled) (Scientific journal of the Fergana State University, 2023)
This article contains information from the pamphlet "Tafsiri Yakubi Charkhi" about the conversations of the mystics Yakubi Charkhi and the relationship between teacher and student. According to Sufi views, after realizing oneself, a person must learn the Sharia knowledge that his teachers taught him, and live with the blessings that he has from God. This idea emphasizes that in the development of a person as a real person, being in society and communicating with good people is of great importance. That is, through conversation, the murid enters the path leading to God.